P709 Early measurement of serum cytokines as predictor of clinical and endoscopic outcome to vedolizumab in patients with ulcerative colitis. (25th January 2019) - Bertani, L; Antonioli, L; Baglietto, L; Tapete, G; Albano, E; Mumolo, M G; Ceccarelli, L; Maltinti, S; Fornai, M; Marchi, S; Blandizzi, C; Costa, F
Abstract: Background: Ulcerative colitis (UC) is characterised by inflammatory cell infiltration of the colonic mucosa with release of pro-inflammatory cytokines. Vedolizumab (VDZ) has been developed to block integrin α4β7 to prevent the homing of activated leucocytes into the inflamed bowel through vascular endothelium. At present, there is a lack of data on the variations of serum cytokine patterns during VDZ treatment in UC patients. Our aim was to correlate serum cytokine levels with treatment outcome in terms of mucosal healing (MH) and clinical remission (CR). Methods: Patients treated with VDZ for moderate–severe UC were enrolled, excluding primary non responders. A blood sample was drawn before VDZ infusion at week 0, 6 and 22, and serum IFN-γ, IL-1β, TNF, IL-6, IL-8, IL-10, IL-12, IL-17A, IL-22 and IL-23 were assessed by a fluorescence assay. At the same time points, faecal calprotectin (FC) and C-reactive protein were assayed. A colonoscopy was performed at baseline and at Week 54, where MH (Mayo Endoscopic Score ≤1) and CR (Partial Mayo Score ≤1) were evaluated. IBD-Q questionnaire was performed at week 0, 6, 22 and 54 to evaluate patient-reported-outcomes. Results: Out of 27 enrolled patients, 6 (22%) experienced loss of response during the first year of treatment. At Week 54, MH was achieved in 12 patients (44%) and CR in 17 (63%). A high value of IL-8 at week 0 correlated with MH ( p < 0.01) after 1 year. A decrease in serum IL-6 and IL-8 at Week 6 correlated with MH ( p < 0.05 and p < 0.001, respectively) and CR ( p < 0.05 for both) after 1 year. At Week 22 the reduction of IL-8 and TNF correlated with MH ( p < 0.001 and p < 0.01, respectively) after 1 year, and the decrease in IL-6, IL-8 and TNF correlated with CR ( p < 0.01 for IL-6 and IL-8, p < 0.05 for TNF) after 1 year. A significant correlation was found also among FC ≤150 mg/g at Week 6 with MH and CR ( p < 0.001 for both) after 1 year. IBD-Q results were correlated to MH and CR only at Week 54. Conclusions: Basal serum levels of IL-8 as well as its decrease over time displayed the best correlation with the therapeutic response to VDZ. In combination with FC and, to a lesser extent, IL-6 and TNF, IL-8 monitoring could help clinicians to implement a better management of patients under treatment with VDZ.